The Importance of Job Satisfaction to improve Employee Performance - Prihadini, Diana; Nurbaity, Siti; Rachmadi, Heksawan; Krishantoro, Krishantoro (Technium Social Sciences Journal, 2021)
Job satisfaction or employee satisfaction is a measure of the level of satisfaction of workers with their type of work which is related to the nature of their job duties, the results of the work achieved, the form of supervision obtained and the feeling of relief and liking for the work they are engaged in. Job satisfaction is an individual thing because each individual will have different levels of satisfaction according to the values that apply in each individual. This study is a qualitative research with a case study approach. Data collection was carried out by means of semi structured interviews to 10 staff working in private universities in Jakarta. Interview was also conducted with 2 HRD directors to dig deeper the efforts to provide job satisfaction which can improve employee performance. The results of this study indicate that job satisfaction has a big role in improving the quality of employee performance.